Understanding global dementia burden: Ageing and dairy supply as key predictors of total, male and female dementia incidence - You, Wenpeng; Henneberg, Maciej; Feng, Shuhuan (Anthropological Review, 2026)
Introduction Dementia incidence is rising worldwide, driven largely by population ageing and demographic transition. Although dietary factors have been proposed as modifiable contributors, the role of dairy consumption remains unclear, with inconsistent findings across regions, populations, and product types. Study aim This study examined whether total dairy supply independently predicts dementia incidence at the population level after accounting for key demographic and socioeconomic indicators. Materials and methods A global ecological analysis was conducted using data from 204 countries. Variables included dairy supply, dementia incidence (total, male, and female), ageing, gross domestic product adjusted for purchasing power parity (GDP PPP), Biological State Index, and urbanisation. Statistical analyses included Pearson and Spearman correlations, partial correlations, principal component analysis, and multivariable linear regression. Enter models were treated as the primary analyses, while stepwise regression was used as an exploratory model-reduction approach. Results Dairy supply showed significant positive correlations with total dementia incidence (r = 0.54, p < 0.001) and with both male and female dementia incidence (r = 0.53, p < 0.001). Ageing showed the strongest associations across all outcomes (r = 0.73–0.78). In the primary multivariable models, ageing remained the strongest independent predictor of total, male, and female dementia incidence. After adjustment, dairy supply remained an independent predictor, with modest effect sizes for total (β = 0.209, p < 0.001), male (β = 0.190, p = 0.001), and female (β = 0.223, p < 0.001) dementia incidence. Urbanisation and genetic vulnerability were associated with dementia incidence at the bivariate level but were not independent predictors in the adjusted models. Exploratory stepwise analyses showed a similar pattern. Conclusions Ageing remained the strongest global predictor of dementia incidence, while dairy supply showed an additional independent association. These findings suggest that nutritional transitions may interact with demographic ageing to shape global dementia patterns worldwide.